2015
DOI: 10.1590/1982-0194201500075
|View full text |Cite
|
Sign up to set email alerts
|

Processo de trabalho e seu impacto nos profissionais de enfermagem em serviço de saúde mental

Abstract: Objective: To analyze the work process and its impact on nursing professionals in a mental health service for the care of drug users. Methods: Cross-sectional study including nursing professionals in a community mental health service. The research instrument was the SATIS-BR and a questionnaire with analysis categories of the work performed. Dialectic hermeneutics was used for the qualitative data. Data were processed and analyzed using the Statistical Package for the Social Sciences. Results: The work overloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
1
11
0
18
Order By: Relevance
“…In this sense, for a better understanding of the nursing work process, as a social practice and destined to an object to be transformed into a product, instruments are used to achieve a specific purpose (7) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, for a better understanding of the nursing work process, as a social practice and destined to an object to be transformed into a product, instruments are used to achieve a specific purpose (7) .…”
Section: Introductionmentioning
confidence: 99%
“…They are: the subprocess work watch; the work subprocess management; the work subprocess teach; the subprocess of job search, and the subprocess of labor participate politically. In this way, a network of division of labor is formed, which refers to the work object, means and instruments, establishing priorities and goals, and evaluating the results achieved (7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study [12] conducted with nursing professionals working in mental health services showed that 75% of nurses said they were moderately overloaded due to the care given to patients. In the same context, the workload related to the physical structure (19.4%), the dynamics of travel and work (13.9%), mental exhaustion (13.8%), fear of physical aggression (11 1%) and verbal abuse (11.1%) of patients were identified.…”
Section: Resultsmentioning
confidence: 99%
“…If the workload is not excessive, and professionals feel emotionally balanced and resolute in their professional activity, there will be greater satisfaction in their daily working day [12]. The efforts of health organizations to improve the quality of management need to mobilize pursuing patient safety and finding ways to work together more effectively and efficiently to ensure that their organizations provide safe, and high-quality care to patients [26].…”
Section: Implications Of Workloads For the Safety Of The Patients In mentioning
confidence: 99%